Audit on the first obstetric ultrasound in a tertiary health facility in the Niger Delta and its implications for maternal foetal care - Abbey, Mkpe; Kua, Paul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The study was prompted by the heterogeneity in the content and the performance of dating or first obstetric ultrasound) scans in Nigeria. The primary aim of the study therefore was to determine whether the conduct of the scans conform to international norms. The secondary goal was to access the implications of the scans for maternal and foetal care. Methods: The study was of mixed design-observational, cross-sectional with audit component, carried out at the Rivers State university teaching hospital (RSUTH), Nigeria from November, 2020 to February 2021. A literature search was carried out on the subject and standards were deduced from the review. 417 consecutive patients were recruited from the antenatal clinic and data on their history and the conduct of the scans were collected. The content of individual scan report was compared with international norms. Data were analysed using Epi. Info 2018 software. Results: There were no guidelines nor uniformity in the conduct of dating or first obstetric ultrasound scans at the RSUTH. Out of the total 408 scan reports, 108 (26.47%) and 300 (73.53) took place inside and outside the RSUTH respectively. The gestational ages at the scans ranged from 8 to 41 weeks. Appropriate biometric parameters were used in 115 (28.19%) reports while in the rest, inappropriate or incomplete parameters were used. Furthermore, the following were not on the menu for the first obstetric scans: determination of chorionicity/amnionicity in multiple pregnancies, anomaly scan, screening for chromosomal abnormalities, foetal growth restriction (FGR), preeclampsia, preterm labour and for morbid adherence of the placenta. The deficiencies in the first obstetric ultrasound would likely lead to wrong dating and inaccurate growth assessment with associated adverse maternal and foetal outcomes, including wrong timing for obstetric interventions and also increased prevalence of those conditions that were not screened for. Conclusions: Absence of guidelines, inaccurate dating and foetal growth assessment and non-performance of important obstetric screening procedures were likely to lead to adverse maternal foetal outcomes. There was therefore urgent need to formulate national guidelines on the subject, adopt effective referral cascade for scans and to introduce practical approach to training in maternal foetal medicine in tertiary institutions in Nigeria.